Study on the Relationship between Conspicuous Need and Group Cultural Identity of Fashion Cultural Consumption - Liang Zhao; Yunze Duan; Qiang Wang; Ke Zhou; Nailin Gu; Xiangzhong Li; Jingyu Dai (Advances in Materials Science and Engineering, 2022)
The consumption of sports and leisure apparel has distinct historical characteristics. It is linked to social fashion and fashion trends, which is an internal expression of college students’ perceptions of sports connotation, aesthetic taste, and community affiliation. Furthermore, it serves as a vital link and conduit for college students’ perceptions of sports fashion. This research includes fieldwork in a sportswear briefing and a thorough interview with 15 interviewees. This research builds an analytical framework for the relationship between sports, leisure clothes, and college students’ consumption behavior based on the conspicuous consumption theory. This article examines the relationship and influence between college students’ consumption behavior and sports and leisure clothing consumption in three categories of community affiliation, perceived value, and consumption behavior. According to the findings, college students’ consuming activity shows off their affluence to a certain extent. But, at its core, college students’ consumption is about understanding society and constructing their self-image. As a result, it reflects the changing value orientation of today’s Chinese college students’ purchasing habits. According to the research, it shows the importance of sports leisure apparel consuming behavior is rooted not only in the clothing but also in community identity.